Biomaterials surface science - Taubert, Andreas; Mano, João F.; Rodríguez-Cabello, J. Carlos (Wiley-VCH, 2013)
The book provides an overview of the highly interdisciplinary field of surface science in the context of biological and biomedical applications. The covered topics range from micro- and nanostructuring for imparting functionality in a top-down manner to the bottom-up fabrication of gradient surfaces by self-assembly, from interfaces between biomaterials and living matter to smart, stimuli-responsive surfaces, and from cell and surface mechanics to the elucidation of cell-chip interactions in biomedical devices.